Fleeing Hitler : France, 1940 - Diamond, Hanna (Oxford Univ. Press, 2007)
Maps x -- Illustrations xi -- The Refugees xii -- Introduction Paris: June 1940 1 -- Part I Exodus -- 1.The Invasion of Paris 15 -- 2.On the Road 53 -- Part II Reactions to Defeat -- 3.Death of the Third Republic 89 -- 4.The Peoples Decisions 112 -- Part III Home or Exile -- 5.SummerAutumn 1940 139 -- 6.Back to Normal? 170 -- Afterword: Forgetting and Remembering the Exodus 203 -- Notes 220 -- Further Reading 241 -- Acknowledgements 246.